Interatrial Block and Electrocardiographic Markers of Repolarization in Patients Hospitalized with COVID-19: Classical and Bayesian Analysis - Rengin CETIN GUVENC; Ali Kaan GUREN; Busra ENGUR; Selin CELİK; Refik DEMIRTUNC (Medeniyet Medical Journal)
Objective: Coronavirus disease-2019 (COVID-19) is associated with atrial fibrillation (AF) and ventricular arrhythmias. Several electrophysiological abnormalities on surface electrocardiography (ECG) are associated with AF and ventricular arrhythmias, either as markers of abnormal interatrial conduction or abnormal repolarization. The present study sought to understand whether such ECG markers are more common in patients hospitalized with COVID-19 infection during the pandemic. Methods: A total of 87 COVID-19 patients formed the study group, whereas 64 patients who were hospitalized for any reason other than COVID-19 infection served as controls. The frequency of partial and advanced interatrial block (IAB), QT and corrected QT (QTc) durations, QT dispersion (QTd), and T peak-to-end duration (Tpe) were measured from ECGs at admission. Results: Both partial and advanced IAB were more common in patients with COVID-19, although statistical significance was only observed for advanced IAB (11.5% in COVID-19 patients vs. 0.0% in controls, p=0.005). There were no differences between the groups for QTc, QTd or Tpe. On Bayesian analyses, there was strong evidence favoring an association between COVID-19 and advanced IAB (BF10: 16), whereas there was no evidence for an association for partial IAB, QTc, QTd, or Tpe (BF10<1 for all). Conclusions: Patients hospitalized with COVID-19 were more likely to have advanced IAB, which may explain why AF is more frequent in these patients.